2018
DOI: 10.1021/acs.jmedchem.8b00258
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Structure–Activity Relationship of HDAC6 Zinc-Finger Ubiquitin Binding Domain Inhibitors

Abstract: HDAC6 plays a central role in the recruitment of protein aggregates for lysosomal degradation and is a promising target for combination therapy with proteasome inhibitors in multiple myeloma. Pharmacologically displacing ubiquitin from the zinc-finger ubiquitin-binding domain (ZnF-UBD) of HDAC6 is an underexplored alternative to catalytic inhibition. Here, we present the discovery of an HDAC6 ZnF-UBD-focused chemical series and its progression from virtual screening hits to low micromolar inhibitors. A carboxy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 33 publications
(61 reference statements)
7
59
0
Order By: Relevance
“…Following our observation that compounds featuring a short carboxylic acid chain can mimic the C-terminal di-glycine carboxylate of ubiquitin and favorably exploit the ZnF-UBD of HDAC6 35,36 , we compiled a virtual library of 9480 in-house and commercially available compounds to screen against USP5 ZnF-UBD. The library was docked using ICM-Pro 37 (Molsoft, CA) and Glide 38 (Schrodinger, NY) to the X-ray crystal structure conformation of USP5 ZnF-UBD (PDB: 2G45) and an alternate conformational state modelled after the structure of HDAC6 ZnF-UBD in complex with inhibitors.…”
Section: Virtual Screen and Hit Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Following our observation that compounds featuring a short carboxylic acid chain can mimic the C-terminal di-glycine carboxylate of ubiquitin and favorably exploit the ZnF-UBD of HDAC6 35,36 , we compiled a virtual library of 9480 in-house and commercially available compounds to screen against USP5 ZnF-UBD. The library was docked using ICM-Pro 37 (Molsoft, CA) and Glide 38 (Schrodinger, NY) to the X-ray crystal structure conformation of USP5 ZnF-UBD (PDB: 2G45) and an alternate conformational state modelled after the structure of HDAC6 ZnF-UBD in complex with inhibitors.…”
Section: Virtual Screen and Hit Identificationmentioning
confidence: 99%
“…Targeting the non-catalytic ZnF-UBD may be an alternative strategy to antagonize USP5 function, similar to the recent development of small molecule inhibitors against the non-catalytic domain of HDAC6 35,36 . Here, we report the structure-based discovery of the first USP5 ZnF-UBD inhibitors and their characterization by 19 F NMR spectroscopy, surface plasmon resonance (SPR) and X-ray crystallography.…”
Section: Introductionmentioning
confidence: 99%
“…ZnF-UBDs share similar sequence and structural folds and the ZnF-UBD of USP3, USP5, USP16 and HDAC6 bind Ub 31,40,[45][46][47] . We have previously shown that the ZnF-UBD of HDAC6 can be targeted by small molecules inhibitors that, as compound 1, include a carboxylic tail mimicking the C-terminal diglycine motif of Ub 48,49 . We therefore decided to use HDAC6 as an anti-target to monitor the selectivity of our compounds.…”
Section: Hit Expansionmentioning
confidence: 99%
“…It has also been revealed that the catalytic His residues can act as general base and acid (110). Furthermore, it is also worthy to note that, intriguingly, HDAC6 is composed of two HDAC domains and a zinc-finger ubiquitin-binding domain (ZnF-UBD) at the C-terminus, making it structurally different from the rest of the HDACs (PDB code: 3C5K) (56,116,117) (Figure 6A).…”
Section: Structural Features and Catalytic Mechanismsmentioning
confidence: 99%
“…Ferreira de Freitas et al recently revealed a novel pharmacological approach to inhibit HDAC6 catalytic activity through the use of small molecules that target the ZnF-UBD (Figure 6A) to prevent the recruitment of ubiquitinated protein aggregates (116,117,140). Further virtual screening and structural studies revealed inhibitor-induced conformational changes of the enzyme that led to the opening of a secondary cavity next to the primary binding pocket (PDB code: 5WBN) (116). This cavity, along with the ZnF-UBD, can thus be exploited for the development of a new class of HDAC6-selective inhibitors with enhanced potency (Figure 6B).…”
Section: Znf-ubd Inhibitorsmentioning
confidence: 99%